Velocity Maximum Speed Analysis on Blackspot Area in Basuki Rachmad Krian - Balongbendo Sidoarjo, Indonesia - Supriyatno, Dadang; Wiwoho Mudjanarko, Sri; Mulyo Utomo, Wahyu (International Journal of Engineering and Technology, 2018)
The existence of the road Basuki Rachmat Krian - Balongbendo is the liaison Surabaya and surrounding areas. Various types of vehicles through Krian-Balongbendo road with high average speed. The big potential is traffic accidents. This study aims to obtain data analysis of the maximum speed in the road. The methodology undertaken in the form of vehicle surveys through the highway. The result of accident rate (AR) analysis on Basuki Rachmat Krian - Balongbendo highway is 201,155496 JPKP. The accident rate for the blackspot (RSP) area is 11.7072. The free flow speed is 63.36 â‰ˆ 63 km / h. Degrees of Saturation (DS) of 0.351 indicates category A service. Actual velocity obtained is 59.80 â‰ˆ 60 km / h. Black Spot Point is located at Km 2000 - 2500 and 2500 - 3000 located on the street Kemangsen. The black side areas are located at Km 1500-3000 and 4500 - 6000 located on Kemagen Road and Balongbendo Highway. These results can describe actual area conditions for safety driving.Â